N-modulin peptides attenuate respiratory distress in a scald-endotoxemia model - Desmond D. Mascarenhas; Puja Ravikumar; Edward P. Amento (Elsevier, 2022)
Introduction: Nephrilin-class peptides, designed inhibitors of Rictor complex, have previously demonstrated efficacy against a wide range of systemic responses to stress, alleviating clinically relevant variables in a rat scald model and sepsis mortality in a mouse model. This study explores the possibility that Nmod3N1vA and Nmod3N1vAS3 peptides, extended versions of a previously reported N-modulin, Nmod3sN1v ("V-nephrilin") can attenuate respiratory distress and associated immunological markers in a male rat scald-endotoxemia model. Methods: Nmod3sN1v peptide was C-terminally extended with a d(AVD) tripeptide to extend the iron-binding pocket. The peptide Nmod3N1vAS3 additionally contains a YLK motif, which has been shown to inhibit STAT3 activation [15]. Rats were treated with each N-modulin peptide (1 mg/kg) by subcutaneous bolus injection on days 1-7 post-burn, then received a single bolus injection of LPS (0.5 mg/ml). Oximeter readings were captured for 4 h thereafter and branchoalveolar lavage (BAL) fluid, lung tissue, plasma and splenocytes were collected at sacrifice. Flow cytometry was performed on splenocytes and BAL cells. Results: d(AVD)-extended Nmod3N1vA showed increased resistance to exoprotease digestion in vitro. Compared to untreated scald control animals and those treated with Nmod3sN1v, Nmod3N1vA and Nmod3N1vAS3 showed differences in biodistribution to lung tissue (<1.0, <1.0, 25.2 and 19.7 ng/mg protein, respectively), respiratory distress (2.52, 2.74, 1.58 and 1.54 distress scores), lung edema (49.2, 43.8, 27.7 and 21.7%), oxidative stress (2.2, 1.5, 1.3 and 1.2 ng/ml plasma OHDG), kidney function (eGFR 0.44, 0.49, 0.62 and 0.71 ml/min/100 g) and weight loss (-7.4%, −9.8%, −5.1% and −5.3%), all variables previously shown to bear upon clinically relevant burn-lung trauma outcomes. Nmod3N1vA and Nmod3N1vAS3 were both significantly more effective (in all cases, p < 0.05) than Nmod3sN1v peptide or control treatments. Conclusion: Although Nmod3sN1v showed efficacy in a rat scald model at 2 mg/kg in a previous study, at the 1 mg/kg dose used in this study, the d(AVD)-extended peptides Nmod3N1vA and Nmod3N1vAS3 were significantly more effective than Nmod3sN1v on a broad range of markers relevant to burn injury and respiratory distress in a rat scald-endotoxemia model.